REGULATING RELIGIOUS LIFE IN MEDAN CITY: An Analysis of Public Policy and Religious Freedom in Medan Major Regulation Number 28/2021 - Kamal, Aulia (Universitas Islam Negeri Imam Bonjol Padang, 2023)
Policies regarding religious life in Indonesia are often problematic, especially PBM Nos. 9 and 8 of 2006. Despite this, this regulation is still adopted and enforced in various cities, including Medan. This article wants to answer the extent of the relevance of Medan Mayor Regulation (Perwal) No. 28 of 2021 concerning Guidelines for Organizing Religious Life and Religious Harmony Forums in the City of Medan as a public policy. This is a literature study using a normative approach, where data is collected from various regulations and literature and then analyzed by borrowing Freedom of Religion and Belief (FoRB) and public policy theory as a theoretical framework. The results show that Perwal needs help at the policy formulation stage. First, policy formulation that does not comply with proceadures is characterized by the absence of evaluation studies or public discussions to develop alternative solution options or improvements to problematic articles. Second, the substance of the policy is without any novelty; apart from Article 9 concerning FKUB funding, this Perwal copies all problematic articles from PBM Nos. 9 and 8 of 2006 without criticism and evaluation. This article argues that the Medan City government needs to revise problematic articles in this Perwal so that its presence becomes relevant and effective. Kebijakan tentang kehidupan beragama di Indonesia seringkali bermasalah, terutama PBM No. 9 dan 8 Tahun 2006. Meskipun demikian, regulasi ini tetap diadopsi dan diberlakukan di berbagai kota, termasuk Medan. Artikel ini ingin menjawab sejauh mana relevansi Peraturan Walikota (Perwal) Medan No. 28 Tahun 2021 tentang Pedoman Penyelenggaraan Kehidupan Umat Beragama dan Forum Kerukunan Umat Beragama di Kota Medan sebagai suatu kebijakan publik. Ini merupakan studi literatur menggunakan pendekatan normatif, di mana data dikumpulkan dari berbagai regulasi dan literatur, kemudian dianalisis dengan meminjam Kebebasan Beragama dan Berkeyakinan (FoRB) dan teori kebijakan publik sebagai kerangka teoritis. Hasilnya menunjukkan bahwa Perwal ini bermasalah pada tahapan formulasi kebijakan. Pertama, perumusan kebijakan yang tidak sesuai prosedur ditandai dengan tidak adanya kajian evaluasi atau diskusi publik untuk mengembangkan pilihan solusi alternatif, atau perbaikan atas pasal-pasal bermasalah. Kedua, substansi kebijakan tanpa ada kebaruan, di mana selain Pasal 9 tentang pendanaan FKUB, Perwal ini menyalin seluruh pasal-pasal bermasalah dari PBM No. 9 dan 8 tahun 2006 tanpa kritik dan evaluasi. Artikel ini berpendapat bahwa pemerintah Kota Medan perlu merevisi pasal-pasal bermasalah dalam Perwal ini agar kehadirannya menjadi relevan dan efektif.